1992
DOI: 10.1093/ije/21.5.877
|View full text |Cite
|
Sign up to set email alerts
|

Familial Aggregation of Oesophageal Cancer in Yangcheng County, Shanxi Province, China

Abstract: Oesophageal cancer is the second most common cause of cancer death in China and is particularly prevalent in northern China. Genetic factors have been studied less than environmental factors in the aetiology of this disease. This study was conducted to evaluate familial aggregation of oesophageal cancer. All households in Yangcheng County were interviewed in 1979 to determine family history of oesophageal cancer. In 1989, vital status for all family members from three Yangcheng villages was determined and re-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 0 publications
4
63
0
Order By: Relevance
“…9,10,17 In our study, increased risk of the ESCC and GCC were found among people with a family history of esophageal cancer, and the risk increased with the number of first-degree relatives who had this disease. The role of genetics in the development of esophageal cancer is also supported by previous reports of familial aggregation of esophageal cancer 29,30 and by one segregation analysis of esophageal cancer pedigrees that suggested an autosomal recessive Mendelian inheritance pattern. 31 Recent molecular studies also support a role for genetic susceptibility in the etiology of ESCC in this area.…”
Section: Discussionsupporting
confidence: 55%
“…9,10,17 In our study, increased risk of the ESCC and GCC were found among people with a family history of esophageal cancer, and the risk increased with the number of first-degree relatives who had this disease. The role of genetics in the development of esophageal cancer is also supported by previous reports of familial aggregation of esophageal cancer 29,30 and by one segregation analysis of esophageal cancer pedigrees that suggested an autosomal recessive Mendelian inheritance pattern. 31 Recent molecular studies also support a role for genetic susceptibility in the etiology of ESCC in this area.…”
Section: Discussionsupporting
confidence: 55%
“…Although epidemiologic studies indicate that tobacco and alcohol consumption are the major risk factors for squamous esophageal cancer in the low-risk regions of Europe and North America, the etiologic agents in high-risk regions have yet to be convincingly identified. Previous studies in high-risk regions showed a strong tendency toward familial aggregation (3,4), suggesting that genetic susceptibility may play a role in the pathogenesis of ESCC.…”
Section: Introductionmentioning
confidence: 91%
“…Esophageal squamous cell carcinoma (ESCC) is very common in many areas of China, especially in Shanxi Province (Hu et al, 1992). In previous studies in Shanxi Province, we found frequent loss of heterozygosity (LOH) on chromosome 13q (Hu et al, 1999.…”
Section: Introductionmentioning
confidence: 99%